UJI KUALITATIF KANDUNGAN BORAKS PADA MAKANAN BAKSO YANG BEREDAR DI PASAR CIJERAH KOTA BANDUNG - Ela Melani MS; Nadiya Nur Afiah Putri Nandika (POLITEKNIK PIKSI GANESHA, 2021)
Borax is a chemical compound derived from heavy metals Boron (B) and is use as an antifungi, wood preservative and antiseptic in cosmetic. The use of boraks as a preservative in food has been banned it is use by the goverment. However the reality is still found the use of borax in food one of them is a meatball. The purpose of this study wich are to identify borax in meatball sold in the Cijerah Market Bandung City. Sampling was carried out on 15 meatball sellers each of 3-5 sample. The samples were identified using a flame test method and reagen test kit borax colour method. Identification experiment result of research meatballs with borax in the samples and test reaction flame no green flame and reagen test kit borax colour method no changes orange colour. So, based on the test the meatballs that are circulating in the Cijerah Market Bandung City negative do not contain borax preservative. So, the meatballs that are circulating in the Cijerah Market Bandung City are safe for society consumption. For further research it is necessary to analysis the nutritional content of meatballs in the Cijerah Market Bandung City as an additional reference and information for the society, and more expanded research area.